(untitled) (Bangladesh Journal of Medical Science, 2012)
Objectives: Acute appendicitis is a condition characterized by inflammation of the appendix for which timely surgery is mandatory to prevent morbidity and mortality. The aim of this study was to assess the differences in incidences, age, sex and seasonal variations and to review the histological diagnoses of all the appendicectomy samples. Methods: A retrospective analysis of patients who underwent appendicectomy at the Hakeem Abdul Hameed Centenary Hospital, New Delhi during the period Jan 2007 to Oct 2010.All the relevant data were retrieved from the accompanying laboratory request forms or patients files records where available. All histology slides were also retrieved and reviewed. To overcome the lack of standardization which is inherent in a retrospective analyses of this type, on review, all the cases were grouped into histopathologic categories Results: Of the 262 cases reviewed, acute suppurative appendicitis accounted for the maximum cases(80,30.53%) and a negative appendicectomy rate of 7% was observed. Male predominance was seen with a M:F ratio of 1.4:1.A peak incidence of 35.1% was observed in the 21-30years age group. A seasonal trend of majority cases being confined to the months of June -August coinciding with the rainy season was noted. Conclusion: The vermiform appendix is a vestigial organ with no specific function. It comes into the limelight when a diagnosis of acute appendicitis is made by the surgeon based upon clinical features and physical examination. Histological examination of the appendix is therefore necessary to assess the surgeon’s rate of negative appendicectomy as well as avoid missing a rare diagnosis or a malignancy. DOI: http://dx.doi.org/10.3329/bjms.v11i3.11722 Bangladesh Journal of Medical Science Vol. 11 No. 03 July12